Progressive web application development by example : develop fast, reliable, and engaging user experiences for the web - Love, Chris (Packt Publishing, 2018)
"Progressive web application development by example helps you explore concepts of the PWA development by enabling you to develop three projects, starting with a 2048 game. In this game, you will review parts of a web manifest file and understand how a browser uses properties to define the home screen experience. You will then move on to learning how to develop and use a podcast client and be introduced to service workers. The application will demonstrate how service workers are registered and updated. In addition to this, you will review a caching API so that you have a firm understanding of how to use the cache within a service worker, and you'll discover core caching strategies and how to code them within a service worker. Finally, you will study how to build a tickets application, wherein you'll apply advanced service worker techniques, such as cache invalidation. Also, you'll learn about tools you can use to validate your applications and scaffold them for quality and consistency. By the end of the book, you will have walked through browser developer tools, node modules, and online tools for creating high-quality PWAs."--Provided by publisher